Roux-en-y gastric bypass attenuates hepatic mitochondrial dysfunction in mice with non-alcoholic steatohepatitis. Issue 4 (10th June 2014) - Verbeek, Jef; Lannoo, Matthias; Pirinen, Eija; Ryu, Dongryeol; Spincemaille, Pieter; Vander Elst, Ingrid; Windmolders, Petra; Thevissen, Karin; Cammue, Bruno P A; van Pelt, Jos; Fransis, Sabine; Van Eyken, Peter; et al.
Abstract : Objective: No therapy for non-alcoholic steatohepatitis (NASH) has been approved so far. Roux-en-y gastric bypass (RYGB) is emerging as a therapeutic option, although its effect on NASH and related hepatic molecular pathways is unclear from human studies. We studied the effect of RYGB on pre-existent NASH and hepatic mitochondrial dysfunction—a key player in NASH pathogenesis—in a novel diet-induced mouse model nicely mimicking human disease. Design: C57BL/6J mice were fed a high-fat high-sucrose diet (HF-HSD). Results: HF-HSD led to early obesity, insulin resistance and hypercholesterolaemia. HF-HSD consistently induced NASH (steatosis, hepatocyte ballooning and inflammation) with fibrosis already after 12-week feeding. NASH was accompanied by hepatic mitochondrial dysfunction, characterised by decreased mitochondrial respiratory chain (MRC) complex I and IV activity, ATP depletion, ultrastructural abnormalities, together with higher 4-hydroxynonenal (HNE) levels, increased uncoupling protein 2 (UCP2) and tumour necrosis factor-α (TNF-α) mRNA and free cholesterol accumulation. In our model of NASH and acquired mitochondrial dysfunction, RYGB induced sustained weight loss, improved insulin resistance and inhibited progression of NASH, with a marked reversal of fibrosis. In parallel, RYGB preserved hepatic MRC complex I activity, restored ATP levels, limited HNE production and decreased TNF-α mRNA. Conclusions: Progression of NASH and NASH-related hepatic mitochondrial dysfunction can be prevented by RYGB. RYGB preserves respiratory chain complex activity, thereby restoring energy output, probably by limiting the amount of oxidative stress and TNF-α. These data suggest that modulation of hepatic mitochondrial function contributes to the favourable effect of RYBG on established NASH.